Medallion „Librarians in time and space”. Perpessicius (Confluenţe Bibliologice, 2025)
The article evokes the life and complex work of Dimitrie P. Panaitescu – Perpessicius, poet, literary critic, editor, bibliologist and academician. Noted for his contributions to the organization and modernization of the Romanian Academy Library, he campaigned for the importance of book legislation and the professionalization of librarians' work. He was the founder of the magazine "Manuscriptum" and the initiator of the Museum of Romanian Literature. One of his landmark achievements was the valorization of Eminescu's manuscripts.
Keywords: Perpessicius (1891 – 1971); Romanian personalities